How to increase sustainable engagement in the workplace through green IS: The role of instructional and motivational design features - Krath, Jeanine; Morschheuser, Benedikt; von Korflesch, Harald F.O.; Hamari, Juho (ECIS 2023 Research Papers, 2023)
Research on green IS has emphasized the value of both instructional and motivational elements in supporting sustainable behavior at work. However, there is still a lack of understanding of these different feature types' individual roles and relevance in inducing sustainable employee behavior. Our study addresses this gap and investigates the use and effects of different instructional and motivational elements in a green IS through a field study with 92 employees in five companies. Our findings based on the analysis of behavioral data shows that instructional elements are more relevant in inducing sustainable behavior, but motivational elements can amplify the positive influence of instructional elements, in particular for long-term user engagement. We contribute to theory and practice by revealing the role of instructional and motivational elements in the successful design of green IS for sustainable employee behavio
Keywords: Green IS; Sustainable behavior; Sustainable employee behavior; Motivation; Learning; Gamification